2016
DOI: 10.1089/neu.2015.3881
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Anti-Glial Fibrillary Acidic Protein Autoantibody Levels during the Acute and Chronic Phases of Traumatic Brain Injury: A Transforming Research and Clinical Knowledge in Traumatic Brain Injury Pilot Study

Abstract: We described recently a subacute serum autoantibody response toward glial fibrillary acidic protein (GFAP) and its breakdown products 5-10 days after severe traumatic brain injury (TBI). Here, we expanded our anti-GFAP autoantibody (AutoAb[GFAP]) investigation to the multicenter observational study Transforming Research and Clinical Knowledge in TBI Pilot (TRACK-TBI Pilot) to cover the full spectrum of TBI (Glasgow Coma Scale 3-15) by using acute (<24 h) plasma samples from 196 patients with acute TBI admitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 53 publications
2
54
0
Order By: Relevance
“…Interestingly, higher levels of GFAP protein have been detected in the blood of patients with neurotrauma, 34 and recent studies have shown that patients with traumatic brain injury have significantly higher levels of autoantibodies against GFAP than healthy controls. 35 Together, these findings may suggest the possibility that astrocytic GFAP enters the circulation after injury to reach the peripheral organs of the immune system (e.g., spleen) where it triggers an autoimmune response culminating in the generation of anti-GFAP autoantibodies.…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, higher levels of GFAP protein have been detected in the blood of patients with neurotrauma, 34 and recent studies have shown that patients with traumatic brain injury have significantly higher levels of autoantibodies against GFAP than healthy controls. 35 Together, these findings may suggest the possibility that astrocytic GFAP enters the circulation after injury to reach the peripheral organs of the immune system (e.g., spleen) where it triggers an autoimmune response culminating in the generation of anti-GFAP autoantibodies.…”
Section: Discussionmentioning
confidence: 95%
“…30 Single blood samples from patients with acute TBI across the full spectrum of injury severity( GCS, 3–8 [n = 25]); GCS, 9–12 [n = 8]; and GCS, 13–15 [n = 163]) were collected within 24 hours of injury. Among these patients with acute TBI, 108 (55.1%) had normal head CT (CT−) scans, while 88 (44.9%) showed CT abnormality (CT+) (Table).…”
Section: Methodsmentioning
confidence: 99%
“…Single blood samples from 21 patients with chronic TBI were collected during the inpatient rehabilitation stay (Table). 30 Sample collection and processing for the TBI and healthy control cohorts were performed identically at all sites (including the commercial vendor for controls) according to the recommendations from the National Institutes of Health–National Institute of Neurological Disorders and Stroke Common Data Elements Biospecimens and Biomarkers Working Group 31 (eMethods in the Supplement provides details). Plasma was extracted after centrifugation of whole blood collected in K2-EDTA blood tubes for 5 minutes at 3000 g .…”
Section: Methodsmentioning
confidence: 99%
“…When the sera of severe TBI patients were screened using brain immunoblots, a significant increase in the amount of GFAP-specific antibodies was detected beginning at day 5 after TBI (Zhang et al, 2014). The concentrations of GFAP-specific autoantibodies were found to be significantly higher in TBI patients compared with healthy controls at 6 months after injury (Wang et al, 2016). In addition, autoantibodies against S100β were detected in the serum of football players during season (Marchi et al, 2013).…”
Section: Biomarkersmentioning
confidence: 99%